A debreceni Kossuth Lajos Tudományegyetem archontológiája (1950–1990) I. rész: Marxizmus–Leninizmus Tanszék, majd Intézet - Mudrák, József (Gerundium, 2013)
THE ARCHONTOLOGY OF LAJOS KOSSUTH UNIVERSITYOF ARTS AND SCIENCES I (1950–1990): THE DEPARTMENT, THEN INSTITUTE OF MARXISM–LENINISM. The archontology of Kossuth University’s Faculty of Arts, Faculty of Sciences, and the so-called central units for the period of January 1, 1950, through December 31, 1990, has been prepared on the basis of the personal cards and the personal iles of the Personnel Department of the Rector’s Oice, and it was supplemented with the less substantially documented yearly arranged material of the Personnel Department for the 1950s. Even so, however, the extant material is not complete; indeed, a totally reliable compilation of the archontology is not possible. Part I is a presentation of the day by day complete list—from institute director (department head) to junior clerk—of the teaching faculty and the non-teaching staf of the interdepartmental institution of the Institute (before 1966: Department) of Marxism–Leninism.